Qualitative comparative analysis of health economic evaluation guidelines for health technology assessment in European countries. (10th December 2020) - Zisis, Konstantinos; Naoum, Panagiota; Athanasakis, Kostas
Abstract: Objective: To classify, analyze, and compare published guidelines for economic evaluation within health technology assessment (HTA) in European countries and highlight differences and similarities. Methods: We performed a literature review to identify published guidance for the conduct and assessment of economic evaluation studies that are undertaken within the context of HTA processes in European countries. Organizations and working groups were identified via the ISPOR, INAHTA, and EUnetHTA databases. Following the identification of official documents, we performed a qualitative content analysis to highlight discrepancies or common practices under the following categories: comparator, perspective on costs/benefits, time horizon, economic evaluation method, instrument used for utility measurement, outcome measure, source for efficacy, modeling, sensitivity analysis, discounting, and incremental cost-effectiveness ratio. Results: A total of nineteen guidance documents were identified (in English) providing data for the analysis in nineteen countries. The comparative content analysis identified common practices in most countries regarding the approaches to the choice of comparator, source of data, the preferred economic evaluation method, the option for a lifetime analytical horizon, discounting, and the choice of key outcome measure—for which, most countries recommend the use of the EQ-5D instrument. Differences were mainly found in the choice of perspective, dealing with uncertainty and sensitivity analysis, the use of end points, and the required use of modeling. Conclusions: The use of economic evaluation constitutes one of the key pillars of the HTA process in Europe. Although a methodological convergence has occurred during the last few years, notable differences still remain.